Identification of Rhizophora mucronata Root in Mangrove Areas with An Anatomical Approach as a Source of Biology Learning - Rohmah, Khafidhotur; Cintamulya, Imas (Biodidaktika : Jurnal Biologi dan Pembelajarannya, 2025)
A study of the anatomy of the roots of Rhizophora mucronata in various waters, such as freshwater, river estuaries, and beaches, has not been widely carried out. Therefore, this study aims to identify the roots of Rhizophora mucronata in the mangrove area with the approach of plant anatomy as a source of learning biology. The root anatomy research method uses the fresh preparation method by making thin transverse sections on the roots and observing them under a microscope. The results of the study showed similarities in the anatomical structure of the roots, namely the epidermis, cortex, endodermis, xylem, and phloem. The difference in the results of this study is in the cortex section, which has a difference in thickness. With this, it can be concluded that there are differences in the anatomy of the roots of Rhizophora mucronata, which live in various waters with differences in the thickness of their cortex cells, and the results of this study can be used as a source of learning in the form of practical instructions. So, it can be concluded that this study can be used as a source of learning for valuable instructions on plant anatomy by students in the course of plant anatomy.